Geochemical Characterization of the Oman Crust‐Mantle Transition Zone, OmanDP Holes CM1A and CM2B. Issue 4 (3rd April 2022) - Kourim, F.; Rospabé, M.; Dygert, N.; Chatterjee, S.; Takazawa, E.; Wang, K.‐L.; Godard, M.; Benoit, M.; Giampouras, M.; Ishii, K.; Teagle, D. A.‐H.; Cooper, M.‐J.; et al.
Abstract: The transition from the gabbroic oceanic crust to the residual mantle harzburgites of the Oman ophiolite has been drilled at Holes CM1A and CM2B (Wadi Tayin massif) during Phase 2 of the International Continental Scientific Drilling Program Oman Drilling Project (November 2017–January 2018). In order to unravel the formation processes of ultramafic rocks in the Wadi Tayin massif crust‐mantle transition zone and deeper in the mantle sections beneath oceanic spreading centers, our study focuses on the whole rock major and trace element compositions (together with CO2 and H2 O concentrations) of these ultramafic rocks (56 dunites and 49 harzburgites). Despite extensive serpentinization and some carbonation, most of the trace element contents (REE, HFSE, Ti, Th, U) record high temperature, magmatic process‐related signatures. Two major trends are observed, with good correlations between (a) Th and U, Nb and LREE on one hand, and between (b) heavy REE, Ti and Hf on the other hand. We interpret the first trend as the signature of late melt/peridotite interactions as LREE are known to be mobilized by such processes (''lithospheric process'') and the second trend as the signature of the initial mantle partial melting (''asthenospheric process''), with little or no overprint from melt/rock reaction events. Plain Language Summary: We focus on the transition from the oceanic crust to the Earth's mantle by studying Holes CM1A and CM2B, drilled in the Oman ophiolite during Phase 2 of the International Continental Scientific Drilling Program Oman Drilling Project. Despite extensive serpentinization and some carbonation, the dunites and harzburgites from the transition zone and the mantle section show a large variability in their petrological and chemical compositions. Results indicate that most of the trace element contents (REE, HFSE, Ti, Th, U) record high temperature, magmatic process‐related signatures. Two major trends are observed, with good correlations between (a) Th and U, Nb and LREE on one hand, and between (b) heavy REE, Ti and Hf on the other hand. We interpret the first trend as the signature of late interactions between a percolating melt and the harzburgites and/or dunites, and the second trend as the signature of the initial mantle partial melting, with little or no overprint from melt/rock reaction events. Key Points: The transition from the oceanic crust to the mantle of Oman has been drilled in the crust‐mantle Holes during Phase 2 of the International Continental Scientific Drilling Project Oman Drilling Project There is large petrological and chemical variability in the dunites and harzburgites from Holes CM1A and CM2B Partial melting versus melt‐rock reaction, and the effects of serpentinization and carbonation of dunites and harzburgites are investigated